2014
DOI: 10.1111/fcp.12079
|View full text |Cite
|
Sign up to set email alerts
|

Single‐ and multiple‐dose tolerability and pharmacokinetics of the CRTH2 antagonist setipiprant in healthy male subjects

Abstract: Chemoattractant receptor-homologous molecule expressed on T helper (Th) 2 cells (CRTH2) is a G-protein-coupled receptor for prostaglandin D2 (PGD2), a key mediator in inflammatory disorders such as asthma and allergic rhinitis. In this study, we investigated the single- and multiple-dose tolerability and pharmacokinetics (PKs) of setipiprant, an orally active, potent, and selective CRTH2 antagonist. This randomized, double-blind, placebo-controlled study was performed in two parts in healthy male subjects. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
5
11
0
Order By: Relevance
“…Assessment of trough setipiprant plasma concentrations at the end of weeks 1 and 2 in the Phase 2 trial indicated that steady-state pharmacokinetics were consistently attained after 1 week of treatment across the dose range assessed, which is in accordance with previous data from healthy subjects [34, 36]. However, both mean and median trough setipiprant concentrations were lower with setipiprant 1000 mg b.i.d.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Assessment of trough setipiprant plasma concentrations at the end of weeks 1 and 2 in the Phase 2 trial indicated that steady-state pharmacokinetics were consistently attained after 1 week of treatment across the dose range assessed, which is in accordance with previous data from healthy subjects [34, 36]. However, both mean and median trough setipiprant concentrations were lower with setipiprant 1000 mg b.i.d.…”
Section: Discussionsupporting
confidence: 87%
“…Previous clinical studies with setipiprant showed a relationship between trough plasma concentration and AUC τ (i.e., AUC during a dosing interval) [34] indicating that trough plasma setipiprant concentrations allow assessment of systemic drug exposure as well as treatment compliance. Trough plasma setipiprant concentrations were therefore used to assess systemic drug exposure and treatment compliance using a validated liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) assay, which had a lower limit of quantification (LLQ) of 1 ng/mL [36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Setipiprant, an orally active and selective CRTH2 antagonist, has been evaluated in a single- and multiple-dose tolerability and pharmacokinetic study in healthy male subjects [74]. Setipiprant was rapidly absorbed and followed a biphasic elimination pattern with a half-life of 10–18 h. The steady-state condition was reached after 2–3 days and the drug was well tolerated, with headache reported as the most frequent adverse event.…”
Section: Clinical Evaluations Of Dp and Crth2 Antagonismmentioning
confidence: 99%
“…In this entry‐into‐humans study, we investigated the tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of single‐ and multiple‐ascending doses of this new compound in healthy subjects over a wide range of doses and in either the presence or absence of food. PK and PD after multiple doses of setipiprant, used as a comparator in view of its similar mode of action, were also investigated at 2 doses (500 and 1000 mg twice a day), the highest of which had previously shown positive results in a proof‐of‐mechanism study as well as in a phase 2 dose‐finding study (http://clinicaltrials.gov registration NCT01484119).…”
mentioning
confidence: 99%